A 9. Sosialisasi Dan Pelatihan Pembuatan Pupuk Organik Kombinasi Gulma Air Dan Kotoran Ayam Di Desa Naning Kecamatan Basarang Kabupaten Kapuas - Ardi Sandriya; Elen Oktavia; Efi Yernisa; Gusnandi Setiawan; Melinda P. Sembiring; Desti Desti; Alfaro Sanggam Pananggar; Dewi Wulandari; Ronal Prasetya; Nesa Angreini Sofhia Sari; Obet Nego Sagala; Stevi Puspita Sari; Nopia Permata Sari Malau; Kepin Sailendro; Leony Fitria Hartantie (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Naning Village has high agricultural potential due to the high rainfall and easy access to water sources. The easy air source and high rainfall cause many weeds to grow. One of the weeds that is often found is kiambang. The purpose of this community service is to socialize and practice the manufacture of compost fertilizer by utilizing weeds that grow in the surrounding area. Compost is made by utilizing kiambang and fermented using EM 4. This process is carried out in 2 stages, namely the stage of preparing raw materials such as kiambang, livestock manure and making EM4 starter and the composting stage, namely the raw materials are chopped about 2-3 cm. All the ingredients are mixed and placed in a closed and dark container so that the aerobic composting process occurs. The result of making this compost is the composting of the materials that have been mixed with parameters of changes in temperature, color, odor, and texture for several days left in a closed container. This change may be related to the drying process and chemical reactions. In addition, there are no rules indicating that the material is in good condition and not infected by insects. This community service was enthusiastically followed by farmer groups in Naning Village. The existence of this socialization and training is expected so that farmer groups can empower surrounding resources to support the agriculture carried out so that they can produce better products and reduce agricultural costs.